Diagnostics and Training of Affordance Perception in Healthy Young Adults—Implications for Post-Stroke Neurorehabilitation - Randerath, Jennifer; Frey, Scott H. (Frontiers in Human Neuroscience, 2016)
Affordance perception is critical to adaptive behavior. It comprises the ability to evaluate whether the environment and the actor’s capabilities enable particular actions. It remains unclear how brain damage and its behavioral sequela impact this ability. Two affordance based judgment tasks were applied in healthy young adults that were adapted for prospective diagnostic purposes in patients. In addition to the commonly analyzed error-rate we included response times and accuracy measures based on a detection theory approach. Moreover, a manipulation was added intended to determine the effectiveness of feedback-based learning. We further applied control tasks that consider whether errors in affordance perception can be explained by errors in perception. Participants responded yes or no to decide prospectively if a given setting would afford a particular action. In study1, 27 participants judged whether their hand would fit through a given aperture [adapted from Ishak, Adolph, & Lin (2008)]. In study2, 19 participants judged whether objects are reachable [adapted from Gabbard, Ammar, & Rodrigues (2005)]. For both studies two sessions were administered. In the first session all participants solved the judgment-task without executing the action. In the second session (feedback manipulation), half of the participants were allowed to first judge and then perform the task for each trial (reach forward and touch the object, or fitting the hand into the aperture). Judgments were slowest and errors most frequent for openings or distances close to the individual’s actual physical limits. With more extreme settings accuracy increased and responses became faster. Importantly, we found an advantageous effect of feedback on performance in both tasks suggesting that affordance perception is rapidly trainable. Further, the aperture task demonstrated that feedback experienced with one hand can transfer to the other. This may have important implications for rehabilitation.